Nuchal Fold Thickness (NFT) in Male versus Female Fetus in Gender Discordant Twins [17E]. (May 2018) - Soni, Shelly; Rochelson, Burton; Blitz, Matthew J.; Vohra, Nidhi; Pessel, Caroline D.
Abstract : INTRODUCTION: To evaluate second trimester nuchal fold thickness (NFT) in male versus female fetuses in gender-discordant dizygotic twin pregnancies. METHODS: Case control study of dizygotic twin pregnancies receiving second trimester fetal nuchal fold measurements identified from a search of ultrasound and cytogenetic databases. Structurally normal fetuses that delivered beyond 30 weeks of gestational age without known chromosomal aberrations were included. NFT was compared in male versus female fetuses using paired t -test. RESULTS: 220 dizygotic twin pregnancies were included. Male fetuses had a higher mean NFT as compared to female fetuses in the entire cohort (3.7 mm in males versus 3.5 mm in females, p < 0.0001, 95% CI 0.3-0.1). Data was stratified based on gestational age. There was a gradual increase in NFT with an increase in gestational age. Male fetuses had a higher NFT through all the gestational ages. CONCLUSION: Male fetuses had a higher mean NFT as compared to female fetuses in gender-discordant dizygotic twin pregnancies.